THE EFFECT OF TAXATION SOCIALIZATION AND TAXPAYER AWARENESS ON COMPLIANCE IN PAYING TWO-WHEEL MOTOR VEHICLE TAX : (Study on Taxpayers at the SAMSAT Office of Bone Bolango Regency) - Wirahayu Putriana Djepu; Zulkifli Bokiu; Victorson Taruh (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of tax socialization and taxpayer awareness on compliance in paying two-wheeled motor vehicle tax at the SAMSAT Office of Bone Bolango Regency. The background of this research is based on the relatively low level of taxpayer compliance, which is indicated by the existence of motor vehicle tax arrears each year. This study employed a quantitative approach using a survey method by distributing questionnaires to two-wheeled motor vehicle taxpayers registered at the SAMSAT Office of Bone Bolango Regency. The data analysis technique used in this research was multiple linear regression analysis with the assistance of statistical software. The results show that partially tax socialization does not have a significant effect on taxpayer compliance in paying two-wheeled motor vehicle tax. Meanwhile, taxpayer awareness has a positive and significant effect on taxpayer compliance. Simultaneously, tax socialization and taxpayer awareness influence taxpayer compliance in paying two-wheeled motor vehicle tax. The results of this study are expected to serve as an evaluation material for the local government and the SAMSAT Office in improving the effectiveness of tax socialization and increasing public awareness in fulfilling tax obligations.